Toward a New Gold Standard for Early Safety: Automated Temperature-Controlled hERG Test on the PatchLiner® - Polonchuk, Liudmila (Frontiers in Pharmacology, 2012)
The Patchliner® temperature-controlled automated patch clamp system was evaluated for testing drug effects on potassium currents through human ether-à-go-go related gene (hERG) channels expressed in Chinese hamster ovary cells at 35–37°C. IC50 values for a set of reference drugs were compared with those obtained using the conventional voltage clamp technique. The results showed good correlation between the data obtained using automated and conventional electrophysiology. Based on these results, the Patchliner® represents an innovative automated electrophysiology platform for conducting the hERG assay that substantially increases throughput and has the advantage of operating at physiological temperature. It allows fast, accurate, and direct assessment of channel function to identify potential proarrhythmic side effects and sets a new standard in ion channel research for drug safety testing.